GEOGRAPHICAL DISTRIBUTION AND SYMPTOMOLOGY OF PLUM POISONING VIRUS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
Currently, the fruit and vegetable industry is developing rapidly among the countries of the world. This is certainly beneficial for the increase in imports and exports and the development of countries. At the same time, pathogenic organisms such as AChV are also spreading rapidly from one region to another. This is a natural phenomenon that leads to the death of many pome fruit plants. This article discusses the countries, plants and symptomatology where Plum pox virus can occur.